Adaptive design of manufacturing process sequences in case of short-term disruptions in the production process. (January 2021) - Bergs, Thomas; Stauder, Lars; Beckers, Alexander; Grünebaum, Timm; Barth, Sebastian
Abstract: Manufacturing companies are more frequently confronted with short-term disruptions due to increasing manufacturing complexity. These disruptions lead to additional costs due to e.g. downtimes. Technological reaction potentials resulting from the adaptation of process parameters are currently neglected when reacting to disruptions. Moreover, technological interrelations between the manufacturing processes are not sufficiently examined. Thus, cost saving potentials are not fully utilized. Therefore, an adaptive reaction is necessary to exploit these potentials. In this paper, three challenges in the adaptive design of manufacturing process sequences in case of short-term disruptions are presented. Furthermore, a concept for overcoming these challenges is outlined.